Inhibition of ohmefentanyl on articular afferent-induced responses of neurons in the spinal lamina X - Zhang Kai-Ming; Yang Huan-Qiao; Zhao Zhi-Qi (Acta Pharmacologica Sinica; Vol 13, No 2 (March 1992): Acta Pharmacologica Sinica, 2016)
In 37 neurons of spinal lamina X, nociceptive responses were evoked by stimulation of the posterior articular nerve (PA) innervating the joint of hindlimb in anesthetized cats. Profound inhibition of nociceptive responses in 73.3% of neurons was induced by ohmefentanyl (1-2 micrograms.kg-1, iv), which was completely reversed by naloxone (80-330 micrograms.kg-1, iv). The results suggested that the mu-opioid receptors was involved in the regulation of transmission of nociceptive information in the spinal lamina X.